Contents of Metal Oxides in Marine Sediment and Rock Samples from the Eastern Libyan Coast, Utilizing the X-ray Method - Citrine El Maleh,; Hamad Hasan,; Hajer Afergani, (AlQalam Journal of Medical and Applied Sciences, 2025)
In this study, the contents of metal oxides and chemical composition of marine sediments were studied in some sediment samples collected from the Eastern coast near Tobrouk region (Libya). Different samples were collected during the summer of 2024. The X-ray method of analysis was used to estimate the types of metal oxides and heavy metal oxides in the studied samples. The results recorded that the samples containing different forms of metal oxides including: (NaO, MgO, Al2O3, SiO2, SO3, CaO, CaCO3, Fe2O3, CuO, and ZnO) and their presents were in percentage as follow: (0.2, 0.7, 1.6, 0.2, 0.6, 11.1, 83.0, 0.1,0.3 and 0.2 %) for the oxides, respectively. On the other side, the same elements oxides were recorded for the Rocks sample, the concentrations of the Metal oxides are: (0.1, 2.3, 1.2, 2.7, 0.6, 10.5, 79.7, 0.5, 0.6, and 0.4%). The findings demonstrated that rocks and sediment samples had substantial concentrations of calcium carbonate (CaCO3) and metal oxides. However, compared to carbonate, the metal oxides (NaO, MgO, Al2O3, SiO2, SO3, CaO, CuO, ZnO, and Fe2O3) in the sediments and rocks of the samples that were recorded had a lower rate of occurrence. Distribution of oxides in both rock and sediments follows the same trend as follows: CaCO3 >> CaO >>MgO >Al2O3 > SO3. This pattern was found to be the same in both x-ray and chemical analysis, indicating significantly high concentrations of Calcium and Carbonates. The presence of some heavy metal oxides is mainly due to the presence of some pollutants as ZnO, CuO, and FeO.